Swachh Survekshan Needs to Clean up its Methodology: An Assessment of Ranks as Performance Incentives for Indian Cities. (November 2021) - Sharma, Karnamadakala Rahul
The Government of India is increasingly using ranks to incentivise sub-units of government. The largest such exercise, the Swachh Survekshan, has been conducted since 2016 and aims to incentivise cities to compete on and improve waste management and sanitation outcomes. Using publicly available Swachh Survekshan data, this article suggests that the current scoring methodology provides weak signals to urban local bodies (ULBs) and citizens on performance metrics. In particular, it shows that the ranks are not consistent and stable across years, there are severe discrepancies in data between components of the awarded score, and that the current methodology favours larger cities. Caution must be exercised, therefore, in interpreting the current methodology as fostering competition. More crucially, a ranking exercise is unlikely to succeed as a policy tool unless it is implemented as one component of a broader effort to improve ULB capacity on managing administrative data.